SCORPIO: A deep survey of radio emission from the stellar life-cycle - Umana, G.; Trigilio, C.; Franzen, Thomas; Norris, R.; Leto, P.; Ingallinera, A.; Buemi, C.; Agliozzo, C.; Cavallaro, F.; Cerrigone, L. (Oxford University Press, 2015)
Radio emission has been detected in a broad variety of stellar objects from all stages of stellar evolution. However, most of our knowledge originates from targeted observations of small samples, which are strongly biased to sources which are peculiar at other wavelengths. In order to tackle this problem we have conducted a deep 1.4 GHz survey by using the Australian Telescope Compact Array, with a net bandwidth of 1.7 GHz (1.4-3.1 GHz) , following the same observing setup as that used for the Australia Telescope Large Area Survey project, this time choosing a region more appropriate for stellar work. In this paper, the Stellar Continuum Originating from Radio Physics In Ourgalaxy (SCORPIO) project is presented as well as results from the pilot experiment. The achieved rms is 30 µJy and the angular resolution ~10 arcsec. 614 point-like sources have been extracted just from the pilot field. Only 34 of them are classified in SIMBAD or the NASA/IPAC Extragalactic Database. About 80 per cent of the extracted sources are reported in one of the inspected catalogues and 50 per cent of them appears to belong to a reddened stellar/Galactic population. However, the evaluation of extragalactic contaminants is very difficult without further investigations. Interesting results have been obtained for extended radio sources that fall in the SCORPIO field. Many roundishlike structures (indicated as bubbles in the following) have been found, some of which are classified at other wavelengths. However, for all of these sources, our project has provided us with images of unprecedented sensitivity and angular resolution.